RANCANG BANGUN MINI VACUUM CLEANER ROBOT DENGAN TRICYCLE DRIVE BERBASIS ARDUINO UNO - Ikhwan Taufik; Herru Santosa Budiono; Fuad Hilmy; Rochmad Eko Prasetyaning Utomo (Scientific Journal of Mechanical Engineering Kinematika, 2023)
Robot technology has penetrated various sectors, including households. One example of robotic innovation for household needs is the vacuum cleaner robot. This research aims to optimize sensor usage while implementing a differential drive system using a tricycle platform consisting of one caster wheel and two differential wheels. Testing was conducted in a space measuring 150 cm Ã— 130 cm with obstacles such as a four-legged chair, cracker crumbs, sunflower seed husks, small pieces of paper, and a handful of dust (flour). The results showed that the robot could navigate quite smoothly and optimally even only using an HC-SR04 ultrasonic sensor. However, more complex challenges within households, such as getting stuck in carpet rolls, handling various types of trash or debris, or moving in narrow spaces, are still aspects that this robot has not fully addressed